Fix Bay'nets: The Regiment in the Hills - Fenn, George Manville, 1831-1909; Groome, William H. C., 1860-1914 (Salt Lake City, UT : Project Gutenberg, 2009)
"Fix Bay'nets: The Regiment in the Hills" by George Manville Fenn is a military adventure novel written in the late 19th century. The story follows the experiences of Her Majesty's 404th Fusiliers as they march through treacherous mountain terrain in the service of the British Empire. The book captures the camaraderie and youthful spirit of the soldiers, particularly focusing on characters like Private Bill Gedge and Lieutenant Bracy, as they face both the challenges of their environment and the threat posed by hostile hill tribes. The beginning of the narrative sets the scene as the regiment makes its arduous ascent through rocky mountain passes, emphasizing their struggles and lighthearted banter amid the rigors of military life. Various characters, including the jovial Private Gedge and the responsible Lieutenant Bracy, are introduced while showcasing their interactions with one another and the challenges they face as part of a young and somewhat inexperienced regiment. As they march, tension builds with the ever-present threat of enemy attacks, leaving the soldiers on alert as they navigate the perils of the hills, culminating in an encounter with hostile forces, reflecting the novel$1 (Bs exploration of bravery, camaraderie, and the harsh realities of military life. The story promises to weave together themes of adventure and personal growth amidst the backdrop of colonial struggles. (This is an automatically generated summary.)s
Release date is 2009-01-27
Produced by Nick Hodson of London, England
Keywords: Historical fiction; Adventure and adventurers -- Juvenile fiction; Great Britain. Army -- Colonial forces -- India -- Juvenile fiction; India -- History -- British occupation, 1765-1947 -- Juvenile fiction; Soldiers -- Juvenile fiction